Improvement of Technology of Liquefaction of Gray Cast Iron Alloy - Saidmakhamadov Nosir; Turakhodjaev Nodir; Abdullaev Kamol; Khasanov Jamshidbek; Tadjiev Nuritdin (Global Scientific Publishing, 2022)
In the article, the technology of liquefaction of thin – walled lifting window detail was developed and summarized. Due to the lack of a model of the lifting sunroof detail, the lifting sunroof detail was first cast in a special vacuum box mold from duralumin alloy using a combustible model. Then it was poured into a sand – clay mold from Ch 24 cast iron alloy. The chemical composition and microstructure of the poured sample were examined using a scanning electron microscope. As a result, a quality cast product was obtained.
Keywords: ferrous metals; gray cast iron; sand